Assessment of Seagrass Beds and Associated Macro-Invertebrates at Cogtong Bay, Philippines: Basis For Conservation And Management - Tuyogon, Tertuliano C. (JPAIR Multidisciplinary Research, 2008)
The seagrass beds in Cogtong Bay were assessed utilizing a set of repeated quarterly assessment. Four representative sites were randomly selected as sampling areas. A 50x50 cm quadrat was used in the assessment along a 50m transect with three replicates per site to determine seagrass % cover, composition and abundance. Commercially important macro-invertebrate associates were assessed using 2m x 50m strip transect. Sediment accretion rate and other environmental parameters were measured. A social component survey was also conducted among seagrass gleaners to corroborate the findings of the actual resource assessment. Results showed that there were only five species of seagrasses in the Bay, Enhalus acoroides, Cymodocea rotundata, C. serrulata, Thalassia hemprichii and Halophila ovalis. E. acoroides was the only species found in sites 1 and 2 (Tabangdio and Calanggaman Islets), while in sites 3 and 4 (North and Northwest sides of Kawasihan Islet) T. hemprichii was the dominant among five species. Diadema setosum and Tripneustes gratilla were the dominant macro-invertebrates. A slight fluctuation of seagrass cover was observed on E. acoroides and T. hemprichii with highest percent cover during the 3rd quarter with 3.46% to only 1.54% during the 4th, and 20.48% cover during the 4th to only 9.58% in the second quarter, respectively. Abundance of invertebrates also fluctuated in November with only 25 from a high of 42 individuals in May. The sediment load was minimal. The results of the socio-economic survey showed that the seagrass beds had significantly benefited the seagrass gleaners in the area.